Latinos and criminal justice: an encyclopedia - Morín, José Luis (Greenwood, 2016)
Concerns about immigration's relationship to crime make accurate information and critical analysis of the utmost importance. This book promotes understanding of Latinas and Latinos and the U.S. criminal justice system, at the same time dispelling popular misconceptions about this population and criminal activity in the United States. Unlike a traditional encyclopedia comprised solely of A-Z entries, this work consists of three parts. Part I offers detailed essays on particularly important topics. Part II provides short, A-Z entries, and Part III gives readers access to resources and key public documents. Topics are cross-referenced to enable easy research. Among the wide range of topics covered are policing and police misconduct, incarceration, the war on drugs, gangs, border crime, and racial profiling. Historically important issues and events relative to the Latino experience of criminal justice in the United States are also included, as are key legal cases